2014
DOI: 10.1007/978-1-4939-1068-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Aberration Test Utilities In Vitro and In Vivo

Abstract: Human populations are frequently exposed to several mutagenic agents that have the potential to damage the DNA, and this, in many cases, may result in the formation of chromosomal aberrations (CAs). CAs are recognized as an important biomarker of human exposure, being a very important tool for environmental biomonitoring. Although there are several types, little is known about the mechanisms involved in the processing of induced lesions in DNA and how these could result in CAs. Thus, cytogenetics and molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…All reads showed to be significant (P<0.001) for all treatment in compare with control. These results reflects that Fasciola hepatica acetone powder have genotoxicity effect leads to these chromosomal aberration like many organic substances derived from other organism like plants with other methods of extraction [25] or for Amoeba parasite [26] but not by acetone powder method. These effects may explain in some manner how carcinogenic property of chronic infection with Fascioliasis above liver of their host which may be related to release of toxic parasite substances through various growing phases of it in parasitized location as for liver in case of liver fluke here.…”
Section: Resultsmentioning
confidence: 91%
“…All reads showed to be significant (P<0.001) for all treatment in compare with control. These results reflects that Fasciola hepatica acetone powder have genotoxicity effect leads to these chromosomal aberration like many organic substances derived from other organism like plants with other methods of extraction [25] or for Amoeba parasite [26] but not by acetone powder method. These effects may explain in some manner how carcinogenic property of chronic infection with Fascioliasis above liver of their host which may be related to release of toxic parasite substances through various growing phases of it in parasitized location as for liver in case of liver fluke here.…”
Section: Resultsmentioning
confidence: 91%
“…In occupational and environmental assessments, the chromosomal aberration test has been utilized for decades as a biomarker of the early impacts of genotoxic agents (Guimaraes et al, 2014; Norppa et al, 2006). Our experimental conclusions showed that these two phthalates caused more clastogenic effects in CHO cells than the vehicle control, as measured by the proportion of aberrant metaphases and the overall number of aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…In occupational and environmental assessments, the chromosomal aberration test has been utilized for decades as a biomarker of the early impacts of genotoxic agents (Guimaraes et al, 2014;Norppa et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Culture initiation was done with 80% of RPMI 1640 media, 20% of FBS, 400µL of Phytohemagglutinin (PHA) and 1ml of peripheral blood was added to the culture flask along with varied concentration of purified sample (50, 100, 200 and 400 µg/ ml) and Positive control ethyl methanesulphonate (EMS) and a media, serum and blood with the PHA was maintained as negative control. 10 The culture flasks were incubated at 37°C for 48 hr with 5% CO 2 . Colchicine (0.2 ml) was added to block the cells in metaphase.…”
Section: Chromosomal Aberration Assaymentioning
confidence: 99%